Analisis Perbandingan Metode Contrast Stretching Dan Histogram Equalization Untuk Memperbaiki Kualitas Citra Digital - Avily, Maulina Adina (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Currently, many people take pictures using digital instruments. However, the resulting images are sometimes not of good quality. To effectively communicate the information contained in the images, a method must be used to enhance image quality. To make an image sharper than the original, the Contrast Stretching technique increases or decreases the contrast (lighting). To produce better images, a technique is used to calculate intensity values and distribute the pixels evenly. This research was conducted to improve image quality using the same technique, but with a different input image, specifically RGB (color image), and the comparison method used was Contrast Stretching. The metrics used in this study are Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR). The software used is MATLAB R2015a.